Stability for the Mixed Type of Quartic and Quadratic Functional Equations. (17th August 2014) - Lee, Young-Su; Kim, Soomin; Kim, Chaewon
Abstract : We establish the general solutions of the following mixed type of quartic and quadratic functional equation:f ( 2 x + y ) + f ( 2 x - y ) = 4 f ( x + y ) + 4 f ( x - y ) + 2 f ( 2 x ) - 8 f ( x ) - 6 f ( y ) . Moreover we prove the Hyers-Ulam-Rassias stability of this equation under the approximately quartic and the approximately quadratic conditions.